2015
DOI: 10.1016/j.alcohol.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between diurnal cycles in locomotor activity, feeding behavior and hepatic PERIOD2 expression in chronic alcohol-fed mice

Abstract: Chronic alcohol consumption contributes to fatty liver disease. Our studies revealed that the hepatic circadian clock is disturbed in alcohol-induced hepatic steatosis, and effects of chronic alcohol administration upon the clock itself may contribute to steatosis. We extended these findings to explore the effects of chronic alcohol treatment on daily feeding and locomotor activity patterns. Mice were chronically pair-fed ad libitum for 4 weeks using the Lieber-DeCarli liquid diet, with calorie-controlled liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Specifically, diurnal locomotor rhythmicity became significantly dampened after switching to ethanol feeding, concurrent with a significant decrease (2.5 times) of nighttime activity and a slight increase of daytime activity in chronic EtOH mice ( Fig. 1 H-K), in agreement with a previous study (18). Of note, liquid diet was replaced daily at zeitgeber time 10 (ZT10) to ZT12 in the current study, and we observed a small bout of locomotor activity during the food refill, most likely because of experimental intervention ( Fig.…”
Section: Chronic Alcohol Consumption Disrupts Circadian Metabolism Andsupporting
confidence: 92%
“…Specifically, diurnal locomotor rhythmicity became significantly dampened after switching to ethanol feeding, concurrent with a significant decrease (2.5 times) of nighttime activity and a slight increase of daytime activity in chronic EtOH mice ( Fig. 1 H-K), in agreement with a previous study (18). Of note, liquid diet was replaced daily at zeitgeber time 10 (ZT10) to ZT12 in the current study, and we observed a small bout of locomotor activity during the food refill, most likely because of experimental intervention ( Fig.…”
Section: Chronic Alcohol Consumption Disrupts Circadian Metabolism Andsupporting
confidence: 92%
“…For example, repeated amphetamine administration increases daytime locomotor activity in adolescent female rats [ 17 ]. Chronic alcohol exposure also increases daytime locomotor activity in mice, eliminating the typical rhythm as well as the peak in activity during the early night [ 79 ]. Over time, drugs of abuse also cause a loss of rhythmicity in self-administration and drug intake.…”
Section: Loss Of Rhythmicity and Loss Of Controlmentioning
confidence: 99%
“…Changes in the alcohol metabolic pathway were observed in a Drosophila Per mutant, resulting in differences in alcohol tolerance and clearance capability64. On the other hand, long-term alcohol intake in mice can lead to changes in the circadian rhythm65, whilst damaging the normal rhythm of liver glycogen metabolism66. Numerous studies have reported such reciprocal regulation of the circadian clock by metabolites, whereby the metabolites regulate expression of core circadian clock genes, thus changing the circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%